Het is wel zo handig om die constructie te gebruiken - Schuurman, Suzanne (Nederlandse Taalkunde, 2025)
Abstract Language is full of expressions that we use instinctively to convey subtle communicative nuances, but whose precise contribution to the meaning of utterances is difficult to pinpoint. This squib argues that Construction Grammar offers a useful framework for capturing these nuances. By identifying the form and meaning of the broader construction in which such expressions appear, we can formulate plausible analyses of how they contribute to meaning beyond the descriptive level, for instance on the level of intersubjectivity. As a case study, I examine the Dutch evaluative wel-zo-construction (‘It is wel zo [ADJ] to do X’), in which the function of the double-negotiation particle wel and the demonstrative adverb zo is unclear. In this corpus-based exploratory study, I argue that this construction is used to positively evaluate some action or behavior in terms of social or practical desirability. As such, the construction is typically used to perform an indirect speech act: encouraging the hearer to behave accordingly, or legitimizing the speaker’s own behavior. Within this constructional framework, I offer new analyses of the functions of wel and zo, by determining how these elements contribute to shaping the performed indirect speech act on the level of intersubjectivity.
Keywords: construction grammar